INTERAKSI SOSIAL ANTARA SESAMA PENGHUNI ASRAMA MAHASISWA UNTAN - Beni M. Sya’ban E.11108032 (FISIP Universitas Tanjungpura, 2013)
The purpose of this research is to to find out how the process of social interaction in everyday life. want to know the form of interaction developed by fellow residents of the dorm surroundings. Want to know the obstacles in dealing with residents in interacting with each other. The type of research used in this research is descriptive, qualitative approach. The results of this research. Thecommunication link between the boarder is going well and also harmonious. Forms of interaction that developed in the environment in the dorm is in the form of cooperation, the accommodation, the dispute or contention. As for the resistance less openness of communication in solving, an attitude of selfishness, of the boarder. Based on the results made a conclusion or advice:. The presence of openness communication in problem solving. Appreciate each other, respect, working together, each other mutual talk, wait until, hold competition, fights, and dissension in all things without harming one with another. Clever put yourself in interact with fellow inhabitant of boarding other.Keywords: social interactions, inhabitant of boarding, students untan